Sensitive method for total selenium determination in garlic and nuts by UV–photochemical vapor generation coupled to atomic absorption spectrometry using mild conditions - Palatnik, Jaime; Londonio, Agustín; Morzán, Ezequiel; Wuilloud, Rodolfo German; Smichowski, Patricia Nora (Academic Press Inc Elsevier Science, 2023)
Fil: Palatnik, Jaime. Comisión Nacional de Energía Atómica; Argentina